On the impact-induced damage in glass fiber reinforced epoxy pipes. (November 2016) - Alshahrani, Rubaian F.; Merah, Nesar; Khan, Shafique M.A.; Al-Nassar, Yagoub
Highlights: Finite element model developed for low velocity impact damage to GFRE composite pipes. The model is employed to investigate the effect of four incident impact energies and two pipe wall thicknesses. Three types of composite failure modes i.e., matrix cracking, delamination and fiber breakage are correlated to the incident impact energy. Abstract: The high mechanical performance of glass-fiber reinforced epoxy (GFRE) pipes and structures may be adversely affected by their low resistance to impact loadings. The low-velocity impact loads are particularly more dangerous as their damage to the structural integrity of the composite pipes often goes undetected. In the present work, a finite element (FE) model of GFRE pipe is developed and used in conjunction with failure criteria based on three-dimensional state of stress to predict layer damage under low-velocity impact. The performance of the numerical model is validated with experimental results. The load–time traces and maximum deflections estimated by FE are found to correlate with the experimentally measured ones. The validated model is then used to predict the composite pipe failure under 12 J, 35 J, 80 J and 110 J and develop damage maps for four incident impact energy levels and two pipe thicknesses. The FE results show that at low impact energy, the damage happens mainly by matrix cracking and delamination, while at intermediate to high energies, fiber breakage occurs, which is in agreement with the experimental results. The damage mechanisms and the severity of the damage under different impact energies are found to correlate well with those obtained experimentally, earlier in this research project.